Ethyl 2-Succinate-Anthraquinone Attenuates Inflammatory Response and Oxidative Stress via Regulating NLRP3 Signaling Pathway - Feng, Burong; Zhao, Xiuye; Zhao, Wei; Jiang, Huiwei; Ren, Zijing; Chen, Yingfu; Yuan, Ye; Du, Zhimin (Frontiers in Pharmacology, 2021)
Aloe-emodin widely possesses antibacterial, anti-inflammatory, antioxidant, antiviral, and anti-infectious properties. This study investigated the effect of ethyl 2-succinate-anthraquinone (Luhui derivative, LHD) on inflammation. In vitro, a THP-1 macrophage inflammation model, made by 100 ng/ml phorbol-12-myristate-13-acetate (PMA) and 1 μg/ml LPS for 24 h, was constructed. The LHD group (6.25 μmol/L, 12.5 μmol/L, 25 μmol/L, 50 μmol/L) had no effect on THP-1 cell activity, and the expression of IL-6 mRNA was down-regulated in a concentration-dependent manner, of which the 25 μmol/L group had the best inhibitory effect. The migration of THP-1 macrophages induced by LPS was decreased by the LHD. Moreover, the LHD suppressed ROS fluorescence expression by inhibiting MDA expression and increasing SOD activity. In vivo, we revealed that the LHD, in different doses (6.25 mg/kg, 12.5 mg/kg, 25 mg/kg, 50 mg/kg), has a protective effect on stress physiological responses by assessing the body temperature of mice. Interestingly, acute lung injury (e.g., the structure of the alveoli disappeared and capillaries in the alveolar wall were dilated and congested) and liver damage (e.g., hepatocyte swelling, neutrophil infiltration, and hepatocyte apoptosis) were obviously improved at the same condition. Furthermore, we initially confirmed that the LHD can down-regulate the expression of NLRP3, IL-1β, and caspase-1 proteins, thereby mediating the NLRP3 inflammasome signaling pathway to produce anti-inflammatory effects. In conclusion, our results indicate that the LHD exerts anti-inflammatory activity via regulating the NLRP3 signaling pathway, inhibition of oxidative stress, and THP-1 macrophage migration.